2020
DOI: 10.1016/j.foodres.2019.108641
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ethylene degreening treatment on sensory properties and consumer response to citrus fruits

Abstract: Degreening treatment is normally applied to early-season citrus varieties grown in the Mediterranean area in order to enhance the external colour when fruits have already reached internal maturity. Despite profound knowledge about the effect of ethylene on the physico-chemical quality of citrus fruit, less is known about its effect on consumers' expectations in the supermarket or consumer quality perceptions when they eat such fruit. In this study, three mandarin cultivars ('Owari', 'Clemenules' and 'Oronules'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 30 publications
7
22
1
Order By: Relevance
“…Furthermore, sweetness and smell were shown to be crucial attributes for respondents, thus revealing a latent prospect for increasing purchasing frequency. Along the lines of studies focused on genetic and agronomic tools influencing the quality of citrus fruits [39][40][41], food scientists and agronomists might also take stock of insights from studies on consumer preferences to develop products with the most requested features.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sweetness and smell were shown to be crucial attributes for respondents, thus revealing a latent prospect for increasing purchasing frequency. Along the lines of studies focused on genetic and agronomic tools influencing the quality of citrus fruits [39][40][41], food scientists and agronomists might also take stock of insights from studies on consumer preferences to develop products with the most requested features.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these authors found that mandarins with yellow-orange skin colouration were more frequently chosen than those with orange skin. More recently, Morales et al [ 8 ] evaluated the effect on consumer preferences of enhancing citrus fruit colouration by applying degreening treatment, and found that consumers preferred the most coloured mandarins with completely orange skin, which disagrees with that previously reported by Campbell et al [ 7 ].…”
Section: Introductionmentioning
confidence: 85%
“…Apart from their flavor and taste, mandarins have particular traits related to convenient consumption, such as seedlessness, easiness to peel or segment separation, which also contribute to their global quality and become more important in recent years for consumer satisfaction. Recently, rind color has been also shown to be a decisive factor for purchase intention [4].…”
Section: Introductionmentioning
confidence: 99%